Bending the Curve: Molecular Manifestations of Electron Antisymmetry. Issue 12 (1st December 2021) - Herzfeld, Judith; Song, Xinrui; Li, Jicun; Li, Pinyuan
Abstract: As very light fermions, electrons are governed by antisymmetric wave functions that lead to exchange integrals in the evaluation of the energy. Here we use the localized representation of orbitals to decompose the electronic energy in a fashion that isolates the enigmatic exchange contributions and characterizes their distinctive control over electron distributions. The key to this completely general analysis is considering the electrons in groups of three, drawing attention to the curvatures of pair potentials, rather than just their amplitudes and slopes. We show that a positive curvature at short distances is essential for the mutual distancing of electrons and a negative curvature at longer distances is essential to account for the influence of lone pairs on bond torsion. Neither curvature is available in the absence of the exchange contributions. Thus, although exchange energies are much shorter range than Coulomb energies, their influence on molecular geometry is profound and readily understood. Abstract : The mutual distancing of electrons in molecules is often attributed to electron charge. However, consideration of the curvature of the distance dependence of different contributions to the electronic energy shows that the mutual distancing actually depends on the required antisymmetry of electron wave functions.